Rickety Stitch and the gelatinous goo. The battle of the bards - Costa, Ben, 1984-; Parks, James (Alfred A. Knopf, 2021)
When Rickety Stitch, the skeleton bard, and his sidekick Goo come upon the city of Harp's Edge, they discover they have arrived just in time for the Battle of the Bards. Rickety soon learns that his troupe must try to beat the famous Percival Dante. But when Rickety finds himself distracted by Canta, a fellow performer, and uncovers dark secrets lurking in the shadows, he and his allies embark on a dangerous quest to save the city.